2020
DOI: 10.22541/au.159585868.87226708
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Not a cakewalk: Insights into movement of large carnivores in human dominated landscapes in India

Abstract: 1.Large carnivore conservation is complex and remains a massive challenge across the world. Owing to their wide-ranging habits, large carnivores encounter various anthropogenic pressures which may potentially lead to conflict. Animal movement is linked with individual fitness as it is important for various biological processes. Therefore, studying how large carnivores adapt their movement to dynamic landscape conditions is vital for management and conservation policy. 2.We first quantified the movement paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Vegetation is dense in most of the areas due to moderate and high rainfall. The Vidarbha region is a tiger hotspot and comprises many national parks and sanctuaries (Habib et al ., 2018). During our study, wolves were found mainly in the buffer of the national parks and sanctuaries.…”
Section: Methodsmentioning
confidence: 99%
“…Vegetation is dense in most of the areas due to moderate and high rainfall. The Vidarbha region is a tiger hotspot and comprises many national parks and sanctuaries (Habib et al ., 2018). During our study, wolves were found mainly in the buffer of the national parks and sanctuaries.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, the fringe areas of many tiger reserves are fraught with incidents of human-tiger conflicts, often leading to the retaliatory killing of tigers. Retaliatory killing and poaching for profit are the biggest threats to tigers in the country (Miquelle et al, 2005;Habib et al, 2017;Dhungana et al, 2018). Persistent conflicts between humans and tigers may also increase the risk of poaching, as people become antagonistic towards tigers, their habitats, and the management that works towards conserving them.…”
Section: Introductionmentioning
confidence: 99%